Pengaruh kemoterapi neoadjuvant terhadap ekspresi NFκB dan c-myc pada karsinoma nasofaring jenis undifferentiated - Farida Nurhayati; Muhardjo M; Made Setiamika; Dyah Ratna Budiani (Oto Rhino Laryngologica Indonesiana, 2012)
Background: Epstein Barr, virus ( EBV ) infection has been frequently related with Nasopharyngeal Carcinoma (NPC), this virus makes the tissue of nasopharyng express Nuclear Factor Kappa Beta  (NFκB). NFκB and c-myc are two transcriptional factor for proliferation. NFκB and c-myc are two sign system for malignancy. The administration of neoadjuvant chemotherapy may prevent the apoptosis and inhibit the proliferation. Purpose: To evaluate the effect of neoadjuvant chemotherapy upon the expression level of NFκB and c-myc in undifferentiated NPC. Method: Quasi Experimental research by one group before and after intervention design. Ten sampels were collected from nasopharyngeal biopsy tissue which had been diagnosed as undifferentiated NPC. Wilcoxon signed Ranks test and Spearman’s were used to analized data, utilizing SPSS 15.0 underwindows program. Result: After neoadjuvant chemotherapy,   there were significant increase (p=0.005) for expression of NFκB (1.11 ± 1.14 / 4.92 ± 2.79) and significant  increase for expression of c-myc (1.15 ± 0,78 / 3.04 ± 1.91). There were significant corelation between  expresion of NFκB and c-myc in undifferentiated NPC (p=0.001). Conclussion: There were significant increase in expression of NFκB and c-myc after neoadjuvant chemotherapy in undifferentiated NPC, and   significant corelation between expresion of NFκB and c-myc in undifferentiated NPC. Keywords: nasopharyngeal carcinoma, neoadjuvant chemotherapy, NFκB and c-myc   Abstrak :  Latar belakang: Patogenesis Karsinoma Nasofaring (KNF) banyak dikaitkan dengan infeksi virus Epstein Barr. Virus ini menyebabkan jaringan mengekspresikan Nuclear Factor Kappa Beta (NFκB). NFκB  dan c-myc merupakan faktor transkripsi, yang menyebabkan proliferasi jaringan. Adanya ekspresi NFκB dan c-myc merupakan dua faktor penting sebagai penanda terjadinya keganasan. Pemberian kemoterapi neoadjuvant diharapkan dapat menghambat proses proliferasi dan menyebabkan terjadinya apoptosis. Tujuan: Mengetahui pengaruh kemoterapi neoadjuvant terhadap ekspresi NFκB dan c-myc pada KNF jenis undifferentiated dan hubungan antara ekspresi NFκB dan c-myc. Metode dan bahan penelitian: Penelitian eksperimen kuasi dengan rancangan one group before and after intervention.  Sebanyak 10 sampel dari jaringan biopsi KNF jenis undifferentiated, masing-masing dilakukan pemeriksaan ekspresi NFκB dan     c-myc sebelum dan sesudah pengobatan. Analisa dengan Uji statistk Wilcoxon signed Ranks test dan Spearman’s menggunakan SPSS 15.0 program underwindow. Hasil penelitian: Setelah kemoterapi neoadjuvant terjadi peningkatan signifikan (p=0,005) ekspresiNFκB (1,11 ± 1,14 dibanding 4,92 ± 2,79) dan terjadi peningkatan signifikan (p=0.025) ekspresi c–myc (1,15 ± 0,78 dibanding 3,04 ± 1,91). Analisis hubungan antara ekspresi NFκB dengan c-myc pada KNF jenis undifferentiated memenuhi garis liniar dan signifikan (p=0,001). Kesimpulan: Terdapat peningkatan ekspresiNFκB dan c-myc sesudah kemoterapi neoadjuvant yang signifikanpada KNF jenis undifferentiated. Terdapat hubungan signifikan antara ekspresi NFκB dengan c-myc pada KNF jenis undifferentiated. Kata kunci: karsinoma nasofaring, kemoterapi neoadjuvant, NFκB dan c-myc